2019
DOI: 10.1080/09571736.2019.1688857
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating language awareness in the foreign language classroom: exploring EFL teaching practices

Abstract: This study reports on EFL teachers' self-reported teaching practices aimed at stimulating students' language awareness. It investigates whether, and to what extent, awareness-raising practices are currently implemented in EFL secondary education in the Netherlands, how these practices can be characterised, and how awareness-raising practices can be developed and further integrated into foreign language education. In a semistructured interview, 10 teachers were asked to provide examples which they believed stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…and language use" (Association for Language Awareness, n.d.), has shown that several techniques enhance language awareness. These techniques, including analytical discussions about language and verbalizing ideas about language (van der Broek et al, 2022), have been shown to impact both cognitive (e.g., awareness of language structures and communicative functions) and affective (e.g., forming language attitudes) levels (Farias, 2005). Language awareness building techniques are present in many second language classrooms and pedagogical materials, potentially leading to greater awareness of one's abilities in the non-dominant language.…”
Section: Comparing the Reliability Of Dominant And Non-dominant Globa...mentioning
confidence: 99%
“…and language use" (Association for Language Awareness, n.d.), has shown that several techniques enhance language awareness. These techniques, including analytical discussions about language and verbalizing ideas about language (van der Broek et al, 2022), have been shown to impact both cognitive (e.g., awareness of language structures and communicative functions) and affective (e.g., forming language attitudes) levels (Farias, 2005). Language awareness building techniques are present in many second language classrooms and pedagogical materials, potentially leading to greater awareness of one's abilities in the non-dominant language.…”
Section: Comparing the Reliability Of Dominant And Non-dominant Globa...mentioning
confidence: 99%
“…Studies have demonstrated that learning quality may decline as a result of reduced stimulation of cognitive processes, and students' achievement may suffer from this (Driessen 2002, Peetsma et al 2006, Van Ewijk & Sleegers 2010, Rjosk et al 2017. The process as presented in Piaget's theory may be linked to language awareness.…”
Section: Linguistic Diversity and Its Role In Students' Learning Achi...mentioning
confidence: 99%
“…Language awareness can be defined as "explicit knowledge about language, and conscious perception and sensitivity in language learning, language teaching and language use" [6]. Raising language awareness (a) can contribute to the development of one's thinking skills within the second language subjects; (b) can help someone gain insight into his/her own process of language learning; and (c) support him/her in connecting the various aspects of language learning [4]. We believe that d/hh people with a deeper understanding of the structures, functions, and mechanisms of their language can approach the study of a second language with more confidence.…”
Section: Language Awareness For the Deafmentioning
confidence: 99%
“…Language awareness provides people with a new sensitivity regarding their language. It can even help them to learn a second language [4].…”
Section: Introductionmentioning
confidence: 99%